PERLINDUNGAN HUKUM PEMEGANG POLIS ASURANSI DALAM MENYELESAIKAN SENGKETA KLAIM ASURANSI - Windy Juli Astuti Ningtyas; Sri Maharani Mardianingrum (Jurnal Ilmiah Wahana Pendidikan, 2023)
It's a reality of life that everyone will eventually be put in danger, whether by other humans or by the forces of nature (in the form of floods, earthquakes, and so on). Insurance is one kind of risk transfer and is often regarded as the best method to manage risk. Having life insurance involves setting aside money in the event of an emergency, which may help to replace lost income. Insurance and other forms of savings may protect a family from financial ruin in the event of an unexpected loss of income. Normative legal research methodology was applied for this study. The discussion's findings demonstrate the interconnectedness of Indonesia's legal protection legislation for policyholders, forming a kind of legal umbrella under which policyholders may exercise their rights. The Indonesian Insurance Mediation and Arbitration Agency (BMAI) may be contacted if a disagreement arises during the claims procedure.